Pengaruh Kompensasi, Lingkungan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada Perusahaan Umum Daerah Air Minum (PERUMDAM) Tirta Kencana Kabupaten Jombang - Lailatus Sa’adah; Tadzarikuz Zaman (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Employee performance has a very important role in the company's progress. Therefore, this research aims to determine the impact of compensation, work environment, and workload on employee performance, with a focus on a case study at the Regional Public Company for Drinking Water (PERUMDAM) Tirta Kencana, Jombang Regency. This research was conducted with the aim of finding out how big the influence is partially or simultaneously, as well as the most significant variables in influencing employee performance. The research method used was multiple linear regression, so that partial results were obtained that the compensation variable had an insignificant effect on employee performance, the work environment variable also had an insignificant effect on employee performance, and the workload variable had a significant effect on employee performance. Then simultaneously the variables of compensation, work environment, and workload simultaneously influence employee performance at the Regional Public Company for Drinking Water (PERUMDAM) Tirta Kencana, Jombang Regency.